Barriers to physical activity participation among students with intellectual disabilities in inclusive schools: a mixed-methods study - Kardiyanto, Deddy Whinata; Ekawati, Febriani Fajar; Rahayu, Tri Winarti; Satyawan, Budhi; Ismaryati (Edu Sportivo: Indonesian Journal of Physical Education, 2026)
Background: Students with intellectual disabilities often encounter significant challenges in participating in physical activities within inclusive school environments; however, limited research has examined how multiple interacting barriers and motivational factors simultaneously influence participation in these settings. Objectives: This study aimed to identify barriers and motivations for physical activity participation among students with intellectual disabilities in inclusive schools.  Methods: A convergent mixed-methods design was employed using purposive sampling. Participants included 32 students with intellectual disabilities, 3 physical education teachers, and 3 sports coaches from three inclusive schools in Surakarta, Indonesia. Data were collected through questionnaires, semi-structured interviews, and observations. Quantitative data were analysed using descriptive statistics, while qualitative data were analysed using thematic analysis. Findings from both datasets were integrated using a triangulation and data-merging strategy to identify convergent and complementary patterns.  Results: The findings revealed three interrelated categories of barriers—physical, social, and environmental. Quantitative results indicated that fatigue (69%), lack of peer support (44%), and limited access to facilities (44%) were the most frequently reported constraints. These factors interacted to reduce participation rather than acting independently. Despite these barriers, students demonstrated strong intrinsic motivation, particularly related to improving health, enhancing well-being, and learning new movement skills. Conclusion: This study contributes to the literature by providing an integrated understanding of how multiple barriers and motivations interact within inclusive school contexts. Addressing these factors through improved accessibility and targeted instructional support is essential to promote sustainable participation in physical activity among students with intellectual disabilities.